2011
DOI: 10.1029/2010ja016260
|View full text |Cite
|
Sign up to set email alerts
|

Energy and fluxes of thermal runaway electrons produced by exponential growth of streamers during the stepping of lightning leaders and in transient luminous events

Abstract: [1] In the present paper, we demonstrate that the exponential expansion of streamers propagating in fields higher than the critical fields for stable propagation of streamers of a given polarity leads to the exponential growth of electric potential differences in streamer heads. These electric potential differences are directly related to the energy that thermal runaway electrons can gain once created. Using full energy range relativistic Monte Carlo simulations, we show that the exponential growth of potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
302
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 203 publications
(318 citation statements)
references
References 75 publications
(136 reference statements)
14
302
1
1
Order By: Relevance
“…One is that seed electrons from cosmic ray ionization of the atmosphere are born with energies in the runaway regime and are further accelerated by the ambient electric field in a cloud, forming a relativistic runaway electron avalanche (RREA; Babich et al, 2012; Dwyer, 2003; Gurevich et al, 1992; Gurevich & Karashtin, 2013; Wilson, 1925) including the feedback mechanism where high‐energy electrons produce high‐energy gamma rays through the bremsstrahlung process which subsequently produces secondary electrons and positrons through photoionization, Compton scattering, or pair production (Dwyer, 2003, 2007; Kutsyk et al, 2011; Skeltved et al, 2014). The other is that thermal (cold) electrons are accelerated into the runaway regime in the high, but very localized, field of streamer tips as well as by the enhanced electric fields in the vicinity of lightning leader tips (Babich et al, 2015; Celestin & Pasko, 2011; Chanrion & Neubert, 2008; Köhn et al, 2014; Köhn & Ebert, 2015; Köhn, Diniz, Harakeh, 2017) and subsequently turn into relativistic RREAs (Carlson et al, 2010, 2006; Köhn, Diniz, Harakeh, 2017; Moss et al, 2006). In the following we explore the streamer mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…One is that seed electrons from cosmic ray ionization of the atmosphere are born with energies in the runaway regime and are further accelerated by the ambient electric field in a cloud, forming a relativistic runaway electron avalanche (RREA; Babich et al, 2012; Dwyer, 2003; Gurevich et al, 1992; Gurevich & Karashtin, 2013; Wilson, 1925) including the feedback mechanism where high‐energy electrons produce high‐energy gamma rays through the bremsstrahlung process which subsequently produces secondary electrons and positrons through photoionization, Compton scattering, or pair production (Dwyer, 2003, 2007; Kutsyk et al, 2011; Skeltved et al, 2014). The other is that thermal (cold) electrons are accelerated into the runaway regime in the high, but very localized, field of streamer tips as well as by the enhanced electric fields in the vicinity of lightning leader tips (Babich et al, 2015; Celestin & Pasko, 2011; Chanrion & Neubert, 2008; Köhn et al, 2014; Köhn & Ebert, 2015; Köhn, Diniz, Harakeh, 2017) and subsequently turn into relativistic RREAs (Carlson et al, 2010, 2006; Köhn, Diniz, Harakeh, 2017; Moss et al, 2006). In the following we explore the streamer mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Because the conductivity of air exponentially increases for intense electric fields the time in which the electric field can persist decrease inversely. As an example, [22] calculates that at ground pressure, fields of 10 MV/m (3·Ek) would have a timescale not higher than the nanosecond. Fields of about 5 MV/m (1.5·Ek) can be sustained for 30 ns.…”
Section: Discussionmentioning
confidence: 99%
“…The fields over Ek would represent an 'overvoltage' case [19] that it might be also produced at the front of negative stepped leader (corona flash [20]). However in reality intense electric fields (>Ek) cannot be persist for a long time because the exponential multiplication of electrons (e.g [21][22]). This time is related to the time of screening of the electric field by charges in a conducting medium (Maxwell relaxation time).…”
Section: Discussionmentioning
confidence: 99%
“…Carlson et al, 2010;Chanrion and Neubert, 2010). The numerical simulation has shown that, at the stage of negative corona flash, the exponential growth of potential differences in streamers can give rise to the production of runaway electrons with energies as high as ∼100 keV (Celestin and Pasko, 2011). Moreover, the electric field produced by stepped leaders can accelerate those energetic electrons up to the MeV energies.…”
Section: V Surkov and M Hayakawa: Underlying Mechanisms Of Transmentioning
confidence: 99%
“…The model of TGF production by runaway breakdown in a strong electric field at the tip of lightning leader channels has been recently studied (Trakhtengertz et al, 2002(Trakhtengertz et al, , 2003Gurevich et al, 2004Gurevich et al, , 2007Dwyer, 2008;Dwyer et al, 2010;Carlson et al, 2010;Celestin and Pasko, 2011). Another promising viewpoint on TGFs supposes that the gamma bursts are generated in thunderclouds as a result of the combined action of runaway breakdown and EASs (Gurevich and Zybin, 2004).…”
Section: V Surkov and M Hayakawa: Underlying Mechanisms Of Transmentioning
confidence: 99%